Relation between structure and piezoelectric properties of (1-x-y)PbZrO3-xPbTiO3-yPb(Ni1/3Nb2/3)O3 ceramics near triple point composition. Issue 16 (December 2016) - Lee, Tae-Gon; Lee, Ho-Jun; Kim, Dae-Hyeon; Xu, HaiBo; Park, Su-jin; Park, Jong-Seong; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin
Abstract: The structural and piezoelectric properties of (1-x-y)PbZrO3 -xPbTiO3 -yPb(Ni1/3 Nb2/3 )O3 [(1-x-y)PZ-xPT-yPNN] ceramics near the triple point were investigated. The 0.16PZ-0.34PT-0.5PNN ceramic with a triple point composition exhibited a large d33, kp and ε33 T /εo values of 855 pC/N, 0.68 and 5800, respectively. However, its g33 and d33 x g33 values were relatively small because of its large ε33 T /εo . Similar results were obtained for specimens with rhombohedral-tetragonal or pseudocubic-tetragonal morphotropic phase boundary (MPB) compositions. However, specimens with a rhombohedral structure near the rhombohedral-tetragonal MPB exhibited large g33 and d33 x g33 values because of their large d33 and small ε33 T /εo that can be explained by their polarization characteristics. In particular, 0.23PZ-0.36PT-0.41PNN ceramic exhibited large g33 and d33 x g33 values of 30.2 × 10 −3 Vm/N and 22.6 × 10 −12 m 2 /N, respectively, thus making it a good candidate for piezoelectric energy harvesters and multilayer actuators.